1993
DOI: 10.1212/wnl.43.12.2501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of vigabatrin on cognitive abilities and quality of life in epilepsy

Abstract: We evaluated the psychological effects of the antiepilepsy drug vigabatrin in a randomized multicenter double-blind placebo-controlled parallel group study that compared 3 grams oral vigabatrin with placebo as daily add-on therapy in patients with focal epilepsy whose complex partial seizures were difficult to control. Testing at baseline and after 12 weeks of vigabatrin (n = 83) or placebo (n = 85) used eight measures of cognitive abilities and three of mood and adjustment. The vigabatrin and placebo groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 0 publications
0
40
1
Order By: Relevance
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 93%
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 93%
“…Vigabatrin has demonstrated few CAEs when compared with placebo in double-blind studies [Dean et al 1999;Dodrill et al 1993;Gillham et al 1993] and fewer adverse effects than carbamazepine in a small, open-label, randomized, parallel-group study . Vigabatrin had no detrimental effects on cognitive functions at 12 months, and memory retrieval and mental flexibility improved significantly.…”
Section: Vigabatrinmentioning
confidence: 99%
“…Only three studies stated the method of randomization, and only one study reported the use of an intention-totreat analysis. Add-on therapy is by nature a heterogeneous treatment category; however, many placebo- controlled add-on trials described subjects' background treatment as "no more than two currently marketed antiepilepsy drugs" (10) or "combinations of drugs" (1 1). To test cognitive effects, many studies used a multitude of neuropsychological tests, the most frequently used of which are listed in Tables 5, 6, and 7, respectively.…”
Section: Resultsmentioning
confidence: 99%